The role of language and culture in Italian language teaching - Madraximova Muborak Abdirasulovna (Universal Teaching and Learning Journal, 2025)
Purpose: The purpose of this study is to examine the interrelationship between language and culture in the process of teaching Italian as a foreign language and to evaluate how the integration of cultural components enhances educational effectiveness and communicative competence. Research Methodology: The study employed a mixed-methods approach. Data were collected through surveys distributed to Italian language teachers and students, complemented by classroom observation. In addition, the cultural content of textbooks and teaching materials was systematically analyzed based on contemporary linguistic and linguoculturology theories. Results: Findings indicate that incorporating cultural context in the teaching of Italian substantially improves learners’ communicative competence and engagement. Specific practices—such as the use of realia, exploration of cultural stereotypes, and reliance on authentic materials—proved particularly effective in fostering intercultural communication skills. Conclusions: The research concludes that language teaching is most effective when combined with cultural integration, as it strengthens both linguistic proficiency and intercultural awareness. Italian language education benefits significantly from adopting culturally informed methodologies. Limitations: The study was limited by its focus on a specific group of teachers and students, which may restrict the generalizability of findings across broader contexts and other foreign languages. Contribution: This research contributes to the field of foreign language teaching methodology by emphasizing the essential role of cultural integration in achieving communicative competence, offering practical strategies that can inform curriculum design and pedagogical practices.